The Semantics of the Preposition “alā” in the Quran: A Conceptual Metaphor Perspective - Sardaraz, Khan; Rashid, Radzuwan Ab; Nusrat, Aasia (Frontiers in Psychology, 2022)
Traditional syntactic approaches do not offer a plausible answer to the use of Arabic preposition ‘ʿalā’ with abstract nouns or states. This paper adopts a corpus based approach to investigate the semantic classification of the preposition ‘ʿalā’ in the Quran from cognitive linguistic perspective. Conceptual metaphor theory (hereafter CMT) was employed to find out conceptual metaphors (hereafter CM) in the data retrieved from the Quran with the help of search Quran software. CMT holds that human sensorimotor neural structures helps in storing the spatial relationships, which is then used to map the abstract concepts in language and thought, and that prepositions are the products of human sensorimotor neural structures. This paper found nine key CM themes behind the use of prepositions in the data, and contact and support schemas were found to be at the heart of both the literal and metaphorical use of the spatial preposition ‘ʿalā’ in the Quran. However, it was also found that language generation and comprehension involve the role of multimodal perceptual schemas and linguistic knowledge rather than unilinear process of one CM. This paper suggests further research into spatial relations across languages to explore the cross cultural implications of image schemas.